2020
DOI: 10.1007/s00345-020-03288-8
|View full text |Cite
|
Sign up to set email alerts
|

Is pre-operative urodynamic bladder function the true predictor of outcome of male sling for post prostatectomy incontinence?

Abstract: Purpose To investigate pre-operative urodynamic parameters in male sling patients to ascertain whether this might better predict surgical outcomes and facilitate patient selection. Methods We performed a retrospective, case notes and video-urodynamics, review of men who underwent AdVanceXP male sling in three London hospitals between 2012 and 2019. Urodynamics were performed in all centres, while retrograde leak point pressure (RLPP) was performed in one centre. Results Successful outcome was seen in 99/130 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…At our institutions, we keep a prospective database of all patients implanted with AdVance™/ AdVance™ XP slings and we build on our outcomes and complications previously published. 8 The AdVance™/ AdVance™ XP sling is the most commonly used male sling in the UK and our reported success rates with AdVance™/AdVance™ XP systems for mild and moderate incontinence, 79% and 72%, respectively, are in keeping with published literature. 6 This study presents a mean 52 (3-112) month follow up for functional, complication and pain outcomes.…”
Section: Further Surgerysupporting
confidence: 85%
See 1 more Smart Citation
“…At our institutions, we keep a prospective database of all patients implanted with AdVance™/ AdVance™ XP slings and we build on our outcomes and complications previously published. 8 The AdVance™/ AdVance™ XP sling is the most commonly used male sling in the UK and our reported success rates with AdVance™/AdVance™ XP systems for mild and moderate incontinence, 79% and 72%, respectively, are in keeping with published literature. 6 This study presents a mean 52 (3-112) month follow up for functional, complication and pain outcomes.…”
Section: Further Surgerysupporting
confidence: 85%
“…The lack of a central register for woman with mesh implants may have led to under‐reporting of complication data. At our institutions, we keep a prospective database of all patients implanted with AdVance™/AdVance™ XP slings and we build on our outcomes and complications previously published 8 . The AdVance™/AdVance™ XP sling is the most commonly used male sling in the UK and our reported success rates with AdVance™/AdVance™ XP systems for mild and moderate incontinence, 79% and 72%, respectively, are in keeping with published literature 6 …”
Section: Discussionmentioning
confidence: 71%
“…However, there is no high level of evidence to support this view. The history of radiotherapy as a negative risk factor has been inconsistently reported in the literature 25–28 . Intuitively, it might inhibit tissue healing and urethral sphincter function, limit the mobility and flexibility of the tissues required for urethral repositioning 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, we do not have data on urodynamic studies. Recent data have suggested that preoperative reduction in bladder capacity less than 250 ml and the detrusor overactivity are indicative of poor results 25 . Patients with underactive bladder are considered to be best treated by AUS, as adequate detrusor contractility is required to urinate against the compressive force of a sling 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria included a need to undergo endourological surgery for stone surgery or a bladder tumor that obliged modifying the ATOMS system filling decided at the time of the final ATOMS adjustment and the impossibility of performing postoperative urodynamic evaluation for technical reasons. The sample size was calculated according to the study by Toia et al [15] performed with a retrobulbar sling. According to that study, we needed a minimum sample size of 54 patients to find the baseline OAB in 27% of continent patients and 55% of incontinent ones after retro-urethral sling implantation, with an alpha error of 5% and a statistical power of 80%.…”
Section: Methodsmentioning
confidence: 99%